2006
DOI: 10.22621/cfn.v120i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Range of Amphibians of the Yukon Territory

Abstract: Four amphibian species occur in the Yukon: Western Toad (Bufo boreas; first verified record in 1961), the Boreal Chorus Frog (Pseudacris maculata, first record in 1995), the Columbia Spotted Frog (Rana luteiventris, first record in 1993), and the Wood Frog (Rana sylvatica; first record in 1933). The Western Toad is restricted to the Liard Basin in five geographically separated areas. Breeding sites have been located on the lower Coal River and vicinity. The Boreal Chorus Frog has been documented from a small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(4 reference statements)
0
5
0
1
Order By: Relevance
“…Multiple studies have confirmed the role of Beringia as a refugium during Pleistocene glaciations (DeChaine, ; Shafer et al ., ) and efforts have been made to understand and explore diversity in the Yukon (e.g. Danks & Downes, ; Boucher & Wheeler, ; Danby, ; Slough & Mennel, ; Slough & Jung, ; Bowden & Buddle, ; Harris & Taylor, ; Danby et al ., ; Klimaszewski et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have confirmed the role of Beringia as a refugium during Pleistocene glaciations (DeChaine, ; Shafer et al ., ) and efforts have been made to understand and explore diversity in the Yukon (e.g. Danks & Downes, ; Boucher & Wheeler, ; Danby, ; Slough & Mennel, ; Slough & Jung, ; Bowden & Buddle, ; Harris & Taylor, ; Danby et al ., ; Klimaszewski et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ces informations seront nécessaires pour assurer la conservation de l'herpétofaune nordique (Slough et Mennell, 2006) dans le contexte où le Nord québécois est appelé à se développer (Gouvernement du Québec, 2014).…”
Section: Facteur Limitant La Répartition Nordiqueunclassified
“…Here we build on previous work to address these shortcomings. The wood frog, Rana sylvatica, is among the earliest amphibians to breed in North America, emerging from winter hibernacula as soon as temperatures exceed freezing (Slough and Mennell, 2006). Wood frogs at our study populations near Norwich Vermont, USA, elevation ca.…”
Section: Introductionmentioning
confidence: 99%